Nitric oxide accumulation is required to protect against iron-mediated oxidative stress in frataxin-deficient Arabidopsis plants - Martin, Mariana Laura (2009)
Frataxin is a mitochondrial protein that is conserved throughout evolution. In yeast and mammals, frataxin is essential for cellular iron (Fe) homeostasis and survival during oxidative stress. In plants, frataxin deficiency causes increased reactive oxygen species (ROS) production and high sensitivity to oxidative stress. In this work we show that a knock-down T-DNA frataxin-deficient mutant of Arabidopsis thaliana (atfh-1) contains increased total and organellar Fe levels. Frataxin deficiency leads also to nitric oxide (NO) accumulation in both, atfh-1 roots and frataxin null mutant yeast. Abnormally high NO production might be part of the defence mechanism against Fe-mediated oxidative stress.